Pengembangan E-Modul Sejarah Lokal Pesisir Selatan Dengan Materi Tentang Kerajaan Inderapura dalam Pembelajaran Sejarah Indonesia Kelas X KD 3.8 - Dandy Tria Sakti; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2021)
Abstract This study aims to develop a local history e-module with material about the Kingdom of Inderapura as part of the local history of Pesisir Selatan Regency. The e-module was developed using the Dick & Carey model, which was then tested for feasibility through a validation stage carried out by 2 lecturers as expert validators of teaching materials and validators of material experts. Practicality tests were also carried out with Indonesian History subject teachers and 15 tenth grade high school students. The results of the validation test by material and teaching materials experts, e-modules can be used in learning, with a rating scale of 1-4, 4 as the maximum value and if below 3 need repair. By material experts, the first stage of the e-module assessment obtained an average score of 3.23 and the second stage obtained a score of 3.88 with an overall average of 3.55. Meanwhile, the teaching materials experts in the first stage of the e-module assessment obtained a score of 3.52 while the second stage was 3.68 and the overall average was 3.6. The results of the practicality test with the teacher showed that the e-module obtained an average practicality value of 3.90 while the e-module students obtained an average practicality value of 3.43583. Thus, based on expert assessments of teaching materials & materials, as well as teacher and student assessments, it shows that the developed e-module is feasible to use. Abstrak Penelitian ini bertujuan untuk mengembangkan e-modul sejarah lokal dengan materi Kerajaan Inderapura sebagai bagian dari sejarah lokal Kabupaten Pesisir Selatan. E-modul dikembangkan dengan model Dick & Carey yang kemudian kelayakannya di uji melalui tahap validasi yang dilakukan oleh 2 dosen sebagai validator ahli bahan ajar dan validator ahli materi. Uji praktikalitas juga dilakukan dengan guru mata pelajaran Sejarah Indonesia dan 15 siswa SMA kelas X. Hasil uji validasi oleh ahli materi dan bahan ajar, e-modul dapat digunakan dalam pembelajaran, dengan skala penilaian 1-4, 4 sebagai nilai maksimal dan jika dibawah 3 memerlukan perbaikan. Oleh ahli materi penilaian tahap pertama e-modul memperoleh skor rata-rata 3,23 dan tahap kedua memperoleh skor 3,88 dengan rata-rata keseluruhan 3,55. Sedangkan oleh ahli bahan ajar pada penilaian tahap pertama e-modul memperoleh skor 3,52 sedangkan tahap kedua 3,68 dan rata-rata keseluruhan 3,6. Hasil uji praktikalitas dengan guru menunjukkan bahwa e-modul memperoleh rata-rata nilai kepraktisan sebesar 3,90 sedangkan dengan peserta didik e-modul memperoleh nilai kepraktisan rata-rata 3,43583. Dengan begitu berdasarkan penilaian ahli bahan ajar & materi, serta penilaian guru dan peserta didik menunjukkan bahwa e-modul yang dikembangkan layak untuk digunakan.